Progress on additive manufacturing technology of solid propellants - Christian Ingabire; Dao-lun Liang; Li-xiang Li (Energetic Materials Frontiers)
The application of Additive Manufacturing (AM) in the production of solid propellants presents new opportunities to enhance the propulsion performance of rockets, missiles, and space launch vehicles. This review highlights recent progress made in AM of solid propellants using Fused Deposition Modeling (FDM), Direct Ink Writing (DIW), and Stereolithography (SLA) AM methods. These AM methods are set to address limitations of traditional casting techniques by providing rapid prototyping capabilities, greater design flexibility, enhanced manufacturing safety, cost savings, and improved rocket performance.Common solid propellant ingredients are examined, with emphasis on recent findings regarding their printability and compatibility with these 3 a.m. processes. The role of thermochemical codes and emerging numerical simulations in predicting propellant material compatibility, performance, and printability is reviewed, alongside important rheological properties essential for solid propellant AM such as material viscosity and yield stress. For each AM method, we also discuss in detail its printing parameters and compatible propellant formulations as well as existing challenges and possible optimization strategies. Furthermore, the mechanical performance and combustion characteristics of additively manufactured solid propellants are thoroughly evaluated.Important milestones are discussed in detail, including the successful manufacturing of AP-based propellants by FDM and the development of photocurable binders such as polyester urethane acrylate (PEUA) with comparable ultimate tensile stress to HTPB propellants and six times higher ultimate tensile strain. The possibilities offered by DIW to produce propellants up to 91 wt% solid loading while maintaining structural integrity are also highlighted. Additionally, developments involving SLA method where APNIMMO-based binders have shown stress at break approximately 10 times greater than traditional HTPB, as well as a 480 % increase in burn rate at 100 MPa compared to non-energetic acrylate resins are highlighted.Remaining challenges and development trends are discussed, including issues in FDM, such as the incompatibility of certain traditional binders with their thermal conditions, brittleness in some AP-based composites, and difficulties in balancing the addition of metallic materials. DIW faces challenges in managing increased viscosity at high solid and energetic content, leading to manufacturing difficulties and the need for binder system optimization. SLA struggles with maintaining resin transparency, balancing mechanical strength with other properties, optimizing curing parameters, and improving the bonding between matrix and solid particles.Future research is expected to focus on developing thermoplastic binders for FDM, exploring energetic copolymer binders and advanced rheological models for DIW, and creating high-energy photopolymer resins while optimizing the SLA process. Additionally, integrating machine learning, exploring the printability of eco-friendly oxidizers, and investigating the printing of solid propellants directly inside motor casings are some of the key future research directions.